CLAVATA modulates auxin homeostasis and transport to regulate stem cell identity and plant shape in a moss - Nemec-Venza, Zoe; Madden, Connor; Stewart, Amy; Liu, Wei; Novák, Ondřej; Pěnčík, Aleš; Cuming, Andrew C; Kamisugi, Yasuko; Harrison, C Jill (The New phytologist, 2022)
The CLAVATA pathway is a key regulator of stem cell function in the multicellular shoot tips of Arabidopsis, where it acts via the WUSCHEL transcription factor to modulate hormone homeostasis. Broad-scale evolutionary comparisons have shown that CLAVATA is a conserved regulator of land plant stem cell function, but CLAVATA acts independently of WUSCHEL-like (WOX) proteins in bryophytes. The relationship between CLAVATA, hormone homeostasis and the evolution of land plant stem cell functions is unknown. Here we show that in the moss, Physcomitrella (Physcomitrium patens), CLAVATA affects stem cell activity by modulating hormone homeostasis. CLAVATA pathway genes are expressed in the tip cells of filamentous tissues, regulating cell identity, filament branching, plant spread and auxin synthesis. The receptor-like kinase PpRPK2 plays the major role, and Pprpk2 mutants have abnormal responses to cytokinin, auxin and auxin transport inhibition, and show reduced expression of PIN auxin transporters. We propose a model whereby PpRPK2 modulates auxin gradients in filaments to determine stem cell identity and overall plant form. Our data indicate that CLAVATA-mediated auxin homeostasis is a fundamental property of plant stem cell function, probably exhibited by the last shared common ancestor of land plants.
Keywords: homeostáza; proteiny huseníčku; Bryophyta; Homeostasis; Arabidopsis Proteins; kyseliny indoloctové; mechy; moss filament identity; Bryopsida; regulace genové exprese u rostlin; Stem Cells; CLAVATA; evo-devo; Indoleacetic Acids; plant stem cell; Gene Expression Regulation, Plant; physcomitrella; kmenové buňky; CLV-WUS